Investigation of nutritional status, life-style and eating habits in vocational Chinese college teachers: A cross-sectional survey - Ji , Chenming; Haq, Ijaz ul; Jing, Miao; Cui, Chunlan; Cheng , Liu; Tian, Qing; Meng, Xiumei; Wu, Qinmin; Jing, Li; Xu, Jelian; Khan, Abbas (Progress in Nutrition, 2021)
Background & objectives.Unhealthy dietary habits might harm teacher’s health. The present study was aimed at college teachers to investigate nutritional status, life-style and eating habits and find the association of nutritional status with the determinants. Methods: A cross-sectional survey was conducted in college teachers, including 33.3% males and 66.7% females. A validated self-administered questionnaire collects information regarding life-style factors and eating habits. Body composition was investigated through bioelectric impedance analysis (BIA). Multinomial and linear regressions were used for the association between dietary habits and nutritional status. Results.Obesity/overweight/high body fats, poor sleep quality and neck and back problems were more common among the respondents. Work/life stress and life-style problems were affecting health status. Animal-source food had a greater risk of increasing BMI (AOR = 2.9, P<0.05) and body fats percentages (AOR = 1.2, P<0.05). Linear regression revealed that balanced eating and exercise has a significant negative association with BMI (ꞵ=-1.34, P<0.05), and WHR (ꞵ=-1.72, P<0.1). Low salt intake was having a negative association with BMI (ꞵ=-1.38, P<0.01), percent body fats (ꞵ=-2.2, P<0.05) and WHR (ꞵ=-0.21, P<0.05). Similarly, low oil intake was negatively associated with BMI (ꞵ=-1.6, P<0.01), percent body fats (ꞵ=-2.1, P<0.05) and WHR (ꞵ=-0.23, P<0.05). Conclusion: Our findings highlight that college teachers had an unhealthy life-style, including overweight and obesity, high body fats percentages, poor sleep quality, inactivity and working stress. Furthermore, dietary habits including balance eating and exercise, low salt and oil positively improve nutritional status while animal-source food negatively improves nutritional status in Chinese college teachers.